2020
DOI: 10.1029/2019jg005239
|View full text |Cite
|
Sign up to set email alerts
|

Trading Water for Carbon: Maintaining Photosynthesis at the Cost of Increased Water Loss During High Temperatures in a Temperate Forest

Abstract: Carbon and water fluxes are often assumed to be coupled as a result of stomatal regulation during dry conditions. However, recent observations evidenced increased transpiration rates during isolated heatwaves across a range of eucalypt species under experimental and natural conditions, with inconsistent effects on photosynthesis (ranging from increases to stark declines). To improve the empirical basis for understanding carbon and water fluxes in forests under hotter and drier climates, we measured the water u… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 75 publications
2
22
1
Order By: Relevance
“…Curves were flatter with a lesser curvature and lower peak of GPP in warm/dry ecosystems with an open forest structure (woodlands and savannas) compared to wetter ecosystems with a more closed forest structure (temperate and tropical forests) where curves were steeper with a greater curvature and higher peak of GPP. While GPP in wooded ecosystems depends upon many factors other than Ta such as Fsd (Hinko‐Najera et al, 2017; Moore et al, 2018), VPD (Griebel et al, 2020; Renchon et al, 2018), soil moisture (Moore et al, 2018), rainfall pulses (Bartsch et al, 2020), abiotic emissions (Bartsch et al, 2020), and canopy dynamics (Wu et al, 2016), our results indicate that the daytime Ta range, MDTa, and ecosystem type partially explain the shape of the GPP–Ta curve. The daytime Ta range sets the overall breadth of the curve (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Curves were flatter with a lesser curvature and lower peak of GPP in warm/dry ecosystems with an open forest structure (woodlands and savannas) compared to wetter ecosystems with a more closed forest structure (temperate and tropical forests) where curves were steeper with a greater curvature and higher peak of GPP. While GPP in wooded ecosystems depends upon many factors other than Ta such as Fsd (Hinko‐Najera et al, 2017; Moore et al, 2018), VPD (Griebel et al, 2020; Renchon et al, 2018), soil moisture (Moore et al, 2018), rainfall pulses (Bartsch et al, 2020), abiotic emissions (Bartsch et al, 2020), and canopy dynamics (Wu et al, 2016), our results indicate that the daytime Ta range, MDTa, and ecosystem type partially explain the shape of the GPP–Ta curve. The daytime Ta range sets the overall breadth of the curve (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Water availability has been shown to moderate stomatal closure under high VPD at TMF-Wom (Griebel et al, 2020) and the strong positive linear relationship between VPD and T opt (Figure SI10b) indicates tolerance to higher VPD in warmer ecoregions.…”
Section: The Gpp-ta Relationship Is Similar Within Ecoregionsmentioning
confidence: 97%
“…6a,b). www.nature.com/scientificreports/ heatwaves in southern Tasmania were mild relative to those recently documented for other heatwaves affecting forest ecosystems in the southern Australian mainland 3,8,18 . This reflected the method used to determine heatwaves in this study-three consecutive days with temperatures above the 90th percentile value for that calendar period-as proposed by Perkins and Alexander 9 -rather than continuous days above an absolute temperature threshold.…”
Section: Resultsmentioning
confidence: 63%
“…Griebel et al (2017) [35] included the summer of 2012-2013, which had exceptionally hot and dry weather, when growth was consistently low across all species. Continued growth during summer might indicate that E. rubida is less sensitive to limitations in soil water availability or higher atmospheric demand for water [78], which might also relate to the higher maximum temperature optima of E. rubida (17 °C) than E. obliqua (15 °C) [40]. Griebel et al (2020) [78] showed that although both species maintained high transpiration rates during a 5-day heatwave, E. rubida exceeded those of E. obliqua.…”
Section: Fixedmentioning
confidence: 99%
“…Continued growth during summer might indicate that E. rubida is less sensitive to limitations in soil water availability or higher atmospheric demand for water [78], which might also relate to the higher maximum temperature optima of E. rubida (17 °C) than E. obliqua (15 °C) [40]. Griebel et al (2020) [78] showed that although both species maintained high transpiration rates during a 5-day heatwave, E. rubida exceeded those of E. obliqua. E. radiata, the species with the least overall growth, had peak stem growth in autumn, which continued, although at a lower rate, into winter.…”
Section: Fixedmentioning
confidence: 99%